Revitalisasi Pembelajaran Bahasa Indonesia melalui Pembentukan Kemampuan Berpikir Kritis dalam Lingkungan Indigenos - Romadhon, Sahrul; Alatas, Mochamad Arifin; Herawati, Yulita (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this study is to find forms of critical thinking skills in an indigenous environment. This is used as an effort to revitalize Indonesian language learning in generation Z. To find these critical thinking skills, the researcher uses Facione's theory of critical thinking which consists of six aspects, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. The research method used in this study is a qualitative research with a grounded theory approach, namely drawing generalizations on the application of a theory, action, or interaction. Meanwhile, the objects of research used were student questions, pre-school and early childhood songs, and traditional games. The result of this research is that there is a revitalization of Indonesian language learning based on critical thinking skills in an indigenous environment by adjusting the environmental style characteristic of generation Z students to face the Era of Society 5.0 who is taking Indonesian language learning. Through this research, it is hoped that it will contribute to the development of Indonesian language learning in the era of society 5.0.